Análisis del medio digital multimedia Wambra. Ec. - Arreaga Herrera, Luis Alberto (2022)
This case study is based on analyzing the content of “WAMBRA.EC” multimedia digital media and its influence on society or part of it. The digital media is from the city of Quito, province of Pichincha; It provides information on events that have taken place in Ecuador and addressing various topics, including politics, the environment, and feminism. That is why the repercussion and incidence of their publications on social networks will be observed and described in this document, incorporating the point of view of several connoisseurs in the journalistic field. the analytical method was used in order to meet the objectives of the study, a focus group was implemented as a tool for two communication graduates, students and people who follow the Wambra medium, this resulted in the strategy used to gain followers is immediacy After reporting the news, an observation sheet was also made on the number of followers, views and comments on their different social networks, resulting in a more significant relationship on their social network Facebook.